The influence of perceived emotional value and visual packaging on purchase intention toward Garnier cosmetics in Batam city - Fitri Anita Simangunsong; Alice Erni Husein (International Journal of Applied Finance and Business Studies, 2026)
This study examines the influence of visual packaging and perceived emotional value on consumers’ purchase intention toward Garnier cosmetics in Batam City. A quantitative approach with a cross-sectional survey design was employed using structured questionnaires distributed to 100 Garnier consumers selected through purposive sampling. Data were analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression, coefficient of determination analysis, and hypothesis testing. The findings indicate that visual packaging and perceived emotional value are perceived positively by consumers and significantly affect purchase intention. Visual packaging has a positive and significant effect on purchase intention (β = 0.232; t = 2.685; p = 0.009), while perceived emotional value exerts a stronger positive and significant effect (β = 0.764; t = 8.345; p = 0.000). Simultaneously, both variables significantly influence purchase intention (F = 327.090; p = 0.000) and explain 86.8% of the variance in purchase intention (Adjusted R² = 0.868). These results demonstrate that attractive packaging and positive emotional experiences play important roles in strengthening consumer buying interest, with perceived emotional value emerging as the dominant determinant of purchase intention toward Garnier cosmetics in Batam City.